Polycystic Ovary Syndrome (PCOS): A risk factor for infertility - Ismajli, Zanita (Orapuh Journal, 2024)
Polycystic Ovary Syndrome (PCOS) is a frequent hormonal disorder in women of reproductive age, which is characterized by irregular and rare menstrual cycles or even high levels of androgens. In women with PCOS, the possibility of various complications increases, including infertility. The main purpose of the review was to provide more information on the relationship between PCOS and infertility and highlight the most important evidence-based recommendations on diagnosis and efficient treatment for PCOS. This review includes the most recent literature sources such as clinical trials, systematic reviews, and meta-analyses (from 2019 to 2022) searched in Web of Science and PubMed databases using terms such as ‘Polycystic Ovary Syndrome’ and ‘infertility’. Articles that did not primarily address PCOS and infertility or those that were just in the pilot trial stage were not included in the review. Based on the literature, infertility is one of the main complications of PCOS, which has been reported in 40% of these cases. According to several evidence-based studies the diagnosis of infertility in PCOS women can be achieved according to the Rotterdam criteria based on the level of anti-Mullerian Hormones, FSH, LH, prolactin, estradiol, and testosterone. Options for management or control of infertility disorders in women with PCOS include stimulation of ovulation, intrauterine insemination as well as cycles of assisted reproductive techniques. On the other hand, the most effective treatments for women with PCOS include the use of metformin, letrozole, and minimally invasive laparoscopic techniques. Nevertheless, because the etiology of PCOS is unknown in most patients, therapy is not always successful. Future studies that concentrate on lifestyle factors and any other external variables that may favorably impact the attainment of suitable therapy are required to provide PCOS patients with appropriate and effective treatment.